2022
DOI: 10.1021/acs.jpca.1c07661
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Thermal Decomposition of 1,1,2,2-Tetramethyldisilane Using Vacuum Ultraviolet Photoionization Time-of-Flight Mass Spectrometry

Abstract: Thermal decomposition of 1,1,2,2-tetramethyldisilane was performed by flash pyrolysis in a SiC microreactor in the temperature range from 295 to 1340 K, followed by molecular beam sampling and vacuum ultraviolet photoionization mass spectrometry analysis. Density functional theory investigations on the energetics of reactants, intermediates, and products were carried out to support the experimental observations. Energetics for 1,1,2,2-tetramethyldisilane initiation decomposition reactions and important seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…and Zagidullin et al, the residence time within the heated region was estimated to be less than 100 μs in this work. , Based on Zagidullin et al, the average pressure within the heated region in the microreactor was estimated to be 10 torr . The reaction conditions within the microreactor significantly favored unimolecular reactions, while bimolecular reactions and wall reactions were reduced. , After exiting the nozzle, the gas mixture, which contained the products, reactive intermediates, and unreacted reactants, supersonically expanded into the main chamber. After being selected by a skimmer, the isolated molecular beam was intercepted by 118 nm VUV radiation in the photoionization region.…”
Section: Experimental and Computational Methodsmentioning
confidence: 63%
See 3 more Smart Citations
“…and Zagidullin et al, the residence time within the heated region was estimated to be less than 100 μs in this work. , Based on Zagidullin et al, the average pressure within the heated region in the microreactor was estimated to be 10 torr . The reaction conditions within the microreactor significantly favored unimolecular reactions, while bimolecular reactions and wall reactions were reduced. , After exiting the nozzle, the gas mixture, which contained the products, reactive intermediates, and unreacted reactants, supersonically expanded into the main chamber. After being selected by a skimmer, the isolated molecular beam was intercepted by 118 nm VUV radiation in the photoionization region.…”
Section: Experimental and Computational Methodsmentioning
confidence: 63%
“…The signal of m / z = 73 (SiC 3 H 9 ) also first appeared at 1140 K, and the origin of this peak was unclear. As previous studies inferred that the ionization cross-section of the m / z = 73 species is large, ,, its barely detectable peak intensity suggested that the m / z = 73 species were negligible in the system. Also, quantum chemistry calculations did not demonstrate any possible unimolecular dissociation channel that could explain the appearance of the m / z = 73 signal. HSi Et 2 EtHSi= normalC normalH 2 + normalC normalH 3 …”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The overall design has been described previously. [21][22][23][24][25][26][27] The vapor of cycloheptane (98%, Sigma Aldrich) was diluted to around 1% in the He carrier gas. The backing pressure of the gas mixture before the pulse valve was 1050 torr.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%